2018
DOI: 10.4236/ojog.2018.81002
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications after Cesarean Delivery: Trends of Incidences, Risk Factors, and Prognosis in a Third Health Level Center in Africa. Case of Gabriel Touré Teaching Hospital

Abstract: Post cesarean infections are the main sources of fever in the postpartum. We have undertaken this study in an African health setting where conditions of working are different from those in developed countries. Objectives: The objectives of this survey were to appreciate incidences, risk factors and prognosis of post cesarean infections. Method: We conducted a randomized historical cohort study in the department of gynecology and obstetrics of Gabriel Touré teaching hospital from 2010 to 2015. Data have been an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In normal group SSI incidence was within expected range, though some studies showed higher incidence. 13,16,17,19 We found total 3 cases of respiratory tract infection and 5 cases of urinary tract infection. Among 5 cases of UTI 3 (8.11%) cases were found in GDM group.…”
Section: Discussionmentioning
confidence: 80%
“…In normal group SSI incidence was within expected range, though some studies showed higher incidence. 13,16,17,19 We found total 3 cases of respiratory tract infection and 5 cases of urinary tract infection. Among 5 cases of UTI 3 (8.11%) cases were found in GDM group.…”
Section: Discussionmentioning
confidence: 80%
“…The most common complication after CS is surgical site infection (SSI), with the rate of other infections ranging from 2-16 % depending on the world region. Antibiotic resistance in the surgical site infection after CS is described [8,9], including resistance to methicillin and carbapenem [10]. Bogdanović et al reported a high prevalence of SSI following CS, and Enterococcus faecalis and Escherichia coli were the most common pathogens isolated in their study [11].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in Ethiopia indicated that maternal complication following cesarean section is higher and mainly related to medical illnesses during pregnancy, urgency of indication, and operation related factors (type of cesarean section performed, length of cesarean section and the type of anesthesia used) ( 19 , 20 ). It is also found that rural residency of the mother, prolonged labor, gestational age, previous history of obstetric complication, parity, and no antenatal care follow up are the contributing factors for an increased maternal complication following cesarean delivery ( 20 23 ).…”
Section: Introductionmentioning
confidence: 99%